2015
DOI: 10.1371/journal.pone.0135691
|View full text |Cite
|
Sign up to set email alerts
|

Overhydration, Cardiac Function and Survival in Hemodialysis Patients

Abstract: Background and objectivesChronic subclinical volume overload occurs very frequently and may be ubiquitous in hemodialysis (HD) patients receiving the standard thrice-weekly treatment. It is directly associated with hypertension, increased arterial stiffness, left ventricular hipertrophy, heart failure, and eventually, higher mortality and morbidity. We aimed to assess for the first time if the relationship between bioimpedance assessed overhydration and survival is maintained when adjustments for echocardiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
100
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(106 citation statements)
references
References 25 publications
2
100
1
3
Order By: Relevance
“…A total of five RCTs (published in six papers 60,61,63,76,77,81 ) and eight non-randomised studies (published in nine papers 30,50,[82][83][84][85][86][87][88] ) were included in the review of clinical effectiveness. There was some question over whether or not the RCTs by Onofriescu et al 81 and Onofriescu et al 60 may be reporting the same trial or outcomes from an overlapping patient population.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of five RCTs (published in six papers 60,61,63,76,77,81 ) and eight non-randomised studies (published in nine papers 30,50,[82][83][84][85][86][87][88] ) were included in the review of clinical effectiveness. There was some question over whether or not the RCTs by Onofriescu et al 81 and Onofriescu et al 60 may be reporting the same trial or outcomes from an overlapping patient population.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The eight non-randomised studies were reported in nine full-text papers, 30,50,[82][83][84][85][86][87][88] with the study by O'Lone et al 82 also reported in a secondary study with an additional 51 participants and a 21-month longer follow-up period. 84 The BCM was the multiple-frequency device used in all eight studies.…”
Section: Non-randomised Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moving patients into the normohydration target range leads to a better control of hypertension (38,39), fewer intradialytic adverse events and improved cardiac function (38,40). Recently Onofriescu et al prospectively conducted a study to investigate the impact of hydration status measured by BCM to all cause mortality and found that the hydration status was associated with the mortality risk in a HD population, independently of cardiac morphology and function (41). In the present study, we found that the proportion of hypervolemic patients evaluated by either clinical, laboratory or bioimpedance methods was significantly higher in the dead group and hypervolemia was an independent risk factor for mortality.…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Nementioning
confidence: 99%